Efforts To Increase Interest In Learning Machine Prime Mover Boats Students Through Learning Method Demonstration In Class X Smk Negeri 1 Sutera Sutera District Of School Year 2015/2016 - Yulhendri Yulhendri (Fakultas Sastra Universitas Ekasakti, 2017)
Basic education is education that underlies secondary education. Shaped elementary education elementary school (SD) and High School (SMP) and secondary education is a continuation of primary education, secondary education consists of general and vocational education. Shaped secondary education schools (SMA) and Vocational High School (SMK). Higher education is an education after secondary education includes educational programs diploma, bachelor's, master's, specialist, and doctoral organized by the college.